Strength Assessment of Corroded Pipelines - Finite Element Simulations and Parametric Studies - Belachew, C.T. (World Scientific Publishing Co. Pte Ltd, 2017)
Pipelines are one of the most efficient means for transporting hydrocarbons from one point to the other. However, there is a great risk of pipelines operation failure due to the detrimental effects of corrosion. At the point of corrosion, the pipe wall becomes thinner and loses its mechanical resistance. In such cases, reliable defect assessment methods are necessary to decide whether to resume continual operation or to shut down for maintenance or replacement. However, the available assessment methods are over-conservative, which enforce either unnecessary maintenance or premature replacement. Furthermore, the defect assessment methods should not only ensure safe operation, but also optimized operation cost. Therefore, a new assessment method was developed based on the nonlinear finite element (FE) analysis and a parametric study of geometric parameters related to the corrosion defect. The new method was validated with burst test database, which can predict the burst pressure of corroded pipelines with better accuracy and consistency. © 2017 World Scientific Publishing Company.